74Relationship of higher-level functional capacity on long-term mortality in Japanese population: NIPPON DATA90. (2nd September 2021) - Nagata, Hideki; Miura, Katsuyuki; Tanaka, Sachiko; Kadota, Aya; Hayakawa, Takehito; Takashima, Naoyuki; Kita, Yoshikuni; Kondo, Keiko; Okayama, Akira; Okamura, Tomonori; Ueshima, Hirotsugu
Abstract: Background: Little is known about the relationships between higher-level functional capacity (HLFC) and mortality, and its gender difference. Methods: NIPPON DATA90 is the cohort study of the National Cardiovascular Survey of Japan in 1990. We followed up 1824 Japanese adults over 65 years who were independent in basic activities of daily living in 1995 until 2010. HLFC was measured in 1995 using the total score and 3 subscales (instrumental activities of daily living [IADL], intellectual activity, social role) by the Tokyo Metropolitan Institute of Gerontology Index of Competence (TMIG-IC). The association of HLFC to mortality was evaluated by adjusted hazard ratio (HR) and 95% confidence interval (CI) using the Cox proportional hazard model. Results: During average 12.2-year follow-up, 836 participants (45.8%) died. Participants with impaired total TMIG-IC score showed significantly higher risk of mortality (adjusted HR 1.37; 95%CI 1.14-1.66) compared with normal participants, even after adjusting for other variables. The corresponding HR was significant only in women (HR 1.42; 95% CI 1.10-1.83). Among the 3 subscales, only impaired social role showed significantly higher risk of mortality (HR 1.37; 95%CI 1.12-1.67) in men. In contrast, IADL and intellectual activity showed significantly higher risk in women (HR 1.51; 95%CI 1.16-1.96) (HR 1.46; 95%CI 1.19-1.80). Conclusions: Impaired HLFC was related to higher risk of long-term mortality in Japanese elderly at baseline. Especially among women, IADL and intellectual activity were important predictors, whereas social role was important in men. Key messages: Impaired HLFC was related to long-term mortality in Japanese elderly.